2016
DOI: 10.1002/stem.2529
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Geminin—A Tale of Two Tails: DNA Replication and Transcriptional/Epigenetic Regulation in Stem Cells

Abstract: Molecular mechanisms governing maintenance, commitment, and differentiation of stem cells are largely unexploited. Molecules involved in the regulation of multiple cellular processes are of particular importance for stem cell physiology, as they integrate different signals and coordinate cellular decisions related with self-renewal and fate determination. Geminin has emerged as a critical factor in DNA replication and stem cell differentiation in different stem cell populations. Its inhibitory interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 96 publications
0
15
0
1
Order By: Relevance
“…Based on earlier analysis, this mutant is expected to show altered ability to form homo and heterodimers with the Geminin family members (Caillat et al, ). It was previously shown that GemC1 forms heterodimers with McIdas and Geminin, whereas Geminin acts antagonistically to GemC1 in the regulation of transcriptional activation of key transcription factors for multiciliogenesis (Arbi et al, ; Caillat et al, ; Caillat et al, ; Kyrousi et al, ; Patmanidi et al, ; Terré et al, ). As Geminin was previously shown to be implicated in stem cell self‐renewal and differentiating decisions (Karamitros et al, ; Spella et al, ), antagonistic roles for Geminin and GemC1 in determining the ependymal cell lineage are likely.…”
Section: Discussionmentioning
confidence: 99%
“…Based on earlier analysis, this mutant is expected to show altered ability to form homo and heterodimers with the Geminin family members (Caillat et al, ). It was previously shown that GemC1 forms heterodimers with McIdas and Geminin, whereas Geminin acts antagonistically to GemC1 in the regulation of transcriptional activation of key transcription factors for multiciliogenesis (Arbi et al, ; Caillat et al, ; Caillat et al, ; Kyrousi et al, ; Patmanidi et al, ; Terré et al, ). As Geminin was previously shown to be implicated in stem cell self‐renewal and differentiating decisions (Karamitros et al, ; Spella et al, ), antagonistic roles for Geminin and GemC1 in determining the ependymal cell lineage are likely.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings from our laboratory, describing the role of two novel molecules McIdas and GemC1/Lynkeas, unravel early events of the molecular pathway governing fate commitment decisions of RGCs to ependymal lineage (Kyrousi et al, 2015. McIdas and GemC1/Lynkeas are coiled-coil proteins which are implicated in cell cycle regulation (Balestrini et al, 2010;Caillat et al, 2015;Pefani et al, 2011) and share homology with Geminin, a protein with a dual role in cell cycle progression and cell differentiation [reviewed in Patmanidi et al (2016)]. More specifically, GemC1/Lynkeas is a key molecule regulating DNA replication via binding to TopBP1 and Cdc45 in order to mediate pre-initiation complex formation (Balestrini et al, 2010), while McIdas controls cell cycle progression through its interaction with Geminin (Caillat et al, 2013;Pefani et al, 2011).…”
Section: Radial Glial Cell Differentiation To Multiciliated Ependymalmentioning
confidence: 99%
“…Geminin is a multi-functional protein, which plays pivotal roles in both DNA replication and transcriptional/epigenetic regulation [9]. Moreover, dysregulation of geminin is often found in various types of human cancers.…”
Section: Introductionmentioning
confidence: 99%